2007
DOI: 10.1136/ard.2007.073544
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of anti-tumour necrosis factor therapy in psoriatic arthritis patients: results from the South Swedish Arthritis Treatment Group register

Abstract: Concomitant MTX and high CRP levels are associated with treatment continuation of anti-TNF therapy in patients with PsA regardless of joint distribution. The positive effect of MTX was primarily linked to fewer dropouts because of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
118
4
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 26 publications
(30 reference statements)
28
118
4
8
Order By: Relevance
“…To further analyze drug tolerability, we examined withdrawal rates during the 24 months of therapy. Other studies in patients with PsA have found that MTX increases the rate of persistence with anti-TNF therapy 6,7,8 and that PsA patients treated with ADA plus MTX have higher serum concentrations of ADA than those treated with ADA alone 16,17 , possibly due to suppression of development of anti-ADA antibody. However, our findings do not support an increased rate of treatment persistence with ADA in patients receiving concomitant MTX.…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…To further analyze drug tolerability, we examined withdrawal rates during the 24 months of therapy. Other studies in patients with PsA have found that MTX increases the rate of persistence with anti-TNF therapy 6,7,8 and that PsA patients treated with ADA plus MTX have higher serum concentrations of ADA than those treated with ADA alone 16,17 , possibly due to suppression of development of anti-ADA antibody. However, our findings do not support an increased rate of treatment persistence with ADA in patients receiving concomitant MTX.…”
Section: Rheumatologymentioning
confidence: 99%
“…There is some evidence that MTX may contribute to improved treatment persistence with anti-TNF therapy 6,7 , particularly when used in combination with infliximab, but there are few data to support a benefit in effectiveness outcomes in patients with PsA treated with concomitant MTX and TNF inhibitors, including adalimumab (ADA) 8,9 . Consequently, the latest European League Against Rheumatism guidelines for the pharmacologic management of PsA include studies of combination therapies with conventional disease-modifying antirheumatic drugs (DMARD) and biologic agents on the research agenda 10 .…”
mentioning
confidence: 99%
“…In particular, hsCRP has been shown to be independently associated with PsA (8), and high CRP levels were shown to protect against treatment termination in both PsA (9) and rheumatoid arthritis trials (see references in [9]). These studies have shown that clinical response and continuation of patients with PsA to treatment are uniformly correlated to the baseline CRP level and that increased systemic inflammation indicates a greater potential for treatment response (9). While there is no clear evidence indicating that CRP level is directly correlated to PsO or PsA disease severity, some studies have suggested a possible relationship.…”
Section: Discussionmentioning
confidence: 99%
“…104 Of these patients, 119 were prescribed etanercept 25 mg twice weekly. In this treatment group, drug continuation was signifi cantly associated with a high CRP at baseline and simultaneous MTX use.…”
Section: Safety In Psoriatic Arthritis Patientsmentioning
confidence: 99%